Pengaruh Model Pembelajaran CTL Type CRH dengan Bantuan Media Teachy.App untuk Meningkatkan Critical Thinking dan Litnum Kelas VI SD Negeri Kalisalam 1: Penelitian - Malqa Dewi Royyana; Didit Yulian Kasdriyanto; Ribut Prastiwi Sri Wijayanti (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Education is closely related to human life and is one of the main elements in creating quality human resources.Literacy and numeracy are knowledge that involve skills not only in reading, writing, and arithmetic.However, literacy and numeracy are related to the ability to solve problems in everyday life (Mulyandani & Hasyda, 2021).The learning model that aligns with the concrete knowledge stage of elementary school students is activity-based and real.One of the interactive learning models is the CTL type CRH, which is a learning model that offers contextual or real learning closely related to students' lives.The research design that will be used is a Pre-Experimental Design in the form of a One Group Pretest-Posttest Design.Based on the results of the Critical Thinking pretest with an average score of 34.81, and after the treatment was given, a posttest was conducted with an average score of 79.63.Meanwhile, for the pretest LitNum, the average score was 36.67, and after the implementation of the CTL Type CRH model, a posttest was conducted with an average score of 77.41.